2003
DOI: 10.1051/0004-6361:20030944
|View full text |Cite
|
Sign up to set email alerts
|

NTT infrared imaging of star cluster candidates towards the central parts of the Galaxy

Abstract: Abstract. We address the issue whether the central parts of the Galaxy harbour young clusters other than Arches, Quintuplet and the Nuclear Young Cluster. A large sample of centrally projected cluster candidates has been recently identified from the 2MASS J, H and K s Atlas. We provide a catalogue of higher angular resolution and deeper images for 57 2MASS cluster candidates, obtained with the near-IR camera SOFI at the ESO NTT telescope. We classify 10 objects as star clusters, some of them deeply embedded in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 28 publications
(51 citation statements)
references
References 27 publications
2
49
0
Order By: Relevance
“…In addition, bright spatially extended emission might be incorrectly classified as unresolved star clusters embedded in nebulae. Confirmation of a real cluster can be achieved through deeper, high-resolution IR photometry or through spectroscopic observations of the candidate stellar members (e.g., Dutra et al 2003b;Borissova et al 2005Borissova et al , 2006Messineo et al 2009;Hanson et al 2010;Davies et al 2012), which in some 18 According to unpublished data, there seem to be more than 300 new clusters detected so far by the UKIDSS team. An independent automated search on UKIDSS, leading to the discovery of 167 additional clusters and multiple star forming regions, has already been published by Solin et al (2012), after the last update of our cluster compilation was done.…”
Section: A4 Spurious Cluster Candidatesmentioning
confidence: 99%
“…In addition, bright spatially extended emission might be incorrectly classified as unresolved star clusters embedded in nebulae. Confirmation of a real cluster can be achieved through deeper, high-resolution IR photometry or through spectroscopic observations of the candidate stellar members (e.g., Dutra et al 2003b;Borissova et al 2005Borissova et al , 2006Messineo et al 2009;Hanson et al 2010;Davies et al 2012), which in some 18 According to unpublished data, there seem to be more than 300 new clusters detected so far by the UKIDSS team. An independent automated search on UKIDSS, leading to the discovery of 167 additional clusters and multiple star forming regions, has already been published by Solin et al (2012), after the last update of our cluster compilation was done.…”
Section: A4 Spurious Cluster Candidatesmentioning
confidence: 99%
“…If the 10-th most massive star of the cluster would have been of B0V type -as proposed by Dutra et al (2003) -the presence of several O stars would be expected. We ruled this out by showing that both the nebular emission and the radio flux are consistent with the brightest stars being B-type.…”
Section: Mass Estimates Of the Db10 And Db11 Clustersmentioning
confidence: 91%
“…The cluster DB11 was already studied in Dutra et al (2003) without the help of spectroscopy and with very different results. After performing statistical field subtraction, the authors identified a much redder main sequence for the region with a color of H − K S ∼ 1.12 mag.…”
Section: Mass Estimates Of the Db10 And Db11 Clustersmentioning
confidence: 99%
See 2 more Smart Citations